(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Justice Delivery effectively and efficiently is the basis of rule of law and governance in a society. It is critical to understand the justice delivery system to fight any crime, particularly a complex and multidimensional crime like human trafficking. In this study, we have discussed the criminal adversarial justice system, criminal inquisitorial justice system, the victim and the police, investigation and victim process, the code of criminal procedure act, 2008, and rights of the victim which is concluded that a highly efficient criminal justice system is required. The Indian criminal justice system is structured in a hierarchy. The Supreme Court, which has original appellate and advisory authority, is at the very top.